1998
DOI: 10.1182/blood.v92.2.362
|View full text |Cite
|
Sign up to set email alerts
|

Evidence for Circulating Bone Marrow-Derived Endothelial Cells

Abstract: It has been proposed that hematopoietic and endothelial cells are derived from a common cell, the hemangioblast. In this study, we demonstrate that a subset of CD34+ cells have the capacity to differentiate into endothelial cells in vitro in the presence of basic fibroblast growth factor, insulin-like growth factor-1, and vascular endothelial growth factor. These differentiated endothelial cells are CD34+, stain for von Willebrand factor (vWF), and incorporate acetylated low-density lipoprotein (LDL). This sug… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
216
1
5

Year Published

2000
2000
2013
2013

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 1,479 publications
(229 citation statements)
references
References 29 publications
7
216
1
5
Order By: Relevance
“…Significant CEC elevation has been observed in AML patients diagnosed with WBC >15G/L and an elevated LDH level; factors known to be associated with large tumor mass and poor prognosis. These findings support the concept that CEC detected in cancer patients may be derived from either angiogenic microvessels or from distant uninvolved vessels activated by tumor secreted cytokines or may be mobilized to the peripheral circulation from the bone marrow (5,15). Our results are in agreement with the first observations of Mancuso et al (9) which revealed that rCEC and aCEC are increased in newly diagnosed breast cancer and lymphoma patients and return to healthy controls levels after cure.…”
Section: Discussionsupporting
confidence: 93%
“…Significant CEC elevation has been observed in AML patients diagnosed with WBC >15G/L and an elevated LDH level; factors known to be associated with large tumor mass and poor prognosis. These findings support the concept that CEC detected in cancer patients may be derived from either angiogenic microvessels or from distant uninvolved vessels activated by tumor secreted cytokines or may be mobilized to the peripheral circulation from the bone marrow (5,15). Our results are in agreement with the first observations of Mancuso et al (9) which revealed that rCEC and aCEC are increased in newly diagnosed breast cancer and lymphoma patients and return to healthy controls levels after cure.…”
Section: Discussionsupporting
confidence: 93%
“…The difference in cell homing between EPCs and RAECs might be explained by different expression levels of CXCR4 by each cell type. Although mature vascular endothelial cells always circulate in peripheral blood, they do not readily incorporate into damaged tissues [37]. Mature endothelial cell transplantation clearly does not affect neovascularization after hind limb ischaemia or myocardial infarction [24,38].…”
Section: Discussionmentioning
confidence: 99%
“…To generate these HBMEC cell lines, primary HBMEC were isolated from a bone marrow aspirate. These cells expressed von Willebrand Factor directly after isolation [28], making it unlikely that these cells were circulating CD34 , von Willebrand Factor-negative precursors of endothelial cells [29]. The HBMEC were immortalised by means of the amphotrophic retroviral construct pLXSN16E6/E7.…”
Section: Discussionmentioning
confidence: 99%